Low-intensity exercise combined with sodium valproate attenuates kainic acid-induced seizures and associated co-morbidities by inhibiting NF-κB signaling in mice - Jia, Yuxiang; Tang, Lele; Yao, Yu; Zhuo, Limin; Qu, Dongxiao; Chen, Xingxing; Ji, Yonghua; Tao, Jie; Zhu, Yudan (Frontiers in Neurology, 2022)
Sodium Valproate (VPA) is the broad-spectrum anticonvulsant that is effective both in adults and children suffering from epilepsy, but it causes psychiatric and behavioral side effects in patients with epilepsy. In addition, 30% of patients with epilepsy develop resistance to VPA. At present, regular physical exercise has shown many benefits and has become an effective complementary therapy for various brain diseases, including epilepsy. Therefore, we wondered whether VPA combined with exercise would be more effective in the treatment of seizures and associated co-morbidities. Here, we used a mouse model with kainic acid (KA)-induced epilepsy to compare the seizure status and the levels of related comorbidities, such as cognition, depression, anxiety and movement disorders, in each group using animal behavioral experiment and local field potential recordings. Subsequently, we investigated the mechanism behind this phenomenon by immunological means. Our results showed that low-intensity exercise combined with VPA reduced seizures and associated comorbidities. This phenomenon seems to be related to the Toll-like receptor 4, activation of the nuclear factor kappa B (NF-κB) and release of interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and IL-6. In brief, low-intensity exercise combined with VPA enhanced the down-regulation of NF-κB related inflammatory response, thereby alleviating the seizures and associated co-morbidities.